New middle Eocene omomyines (Primates, Haplorhini) from San Diego County, California. Issue 124 (November 2018) - Atwater, Amy L.; Kirk, E. Christopher
Abstract: The Friars Formation of San Diego County, California, has yielded a middle Eocene mammalian fauna from the early part of the Uintan North American Land Mammal Age. Prior research on the primate fauna from the Friars Formation provides evidence of one notharctine and multiple omomyine species, but many specimens collected since the early 1980s remain unstudied. Here we describe three new omomyine genera from the Friars Formation. These new taxa range in estimated body mass from about 119 g to 757 g, and substantially expand the diversity of middle Eocene omomyoids known from Southern California. Resolution of the phylogenetic relationships of the new Friars Formation omomyines is complicated by the fact that different character-taxon matrices and tree building methods produce different results. Nevertheless, all preliminary phylogenetic analyses are congruent in recovering a close relationship between the three new genera and the omomyines Macrotarsius, Omomys, Ourayia, and Utahia . Prior research has documented a shift in omomyoid diversity in North America from the anantomophine-rich Bridgerian to the omomyine-rich Uintan. Our description of three new Uintan omomyine taxa from the Friars Formation further emphasizes these opposite trends in anaptomorphine and omomyine species richness during the middle Eocene. All three of the new taxa are currently known from only the Friars Formation in San Diego County, California. Four of the previously known omomyoid genera from Southern California ( Dyseolemur, Chumashius, Yaquius, and Stockia ) are also endemic to the region, further highlighting the provincial character of primate faunas in Utah, Southern California, and West Texas during the Uintan.